2020
DOI: 10.1155/2020/6267472
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Analysis of the Flow inside the Submerged Entry Nozzle

Abstract: The quality of steel produced by continuous casting depends mainly on the characteristics of the liquid steel flow pattern within the mold. This pattern depends on the flow dynamics of the nozzle that is immersed in liquid steel. This work characterizes the fluid dynamics within two separate submerged entry nozzle models with a square cross section bore. The Froude similarity criterion and water as working fluid have been used. The models consist of a square-shaped tube with one inlet and two lateral squared e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
(44 reference statements)
2
11
0
Order By: Relevance
“…We refer to this fluid flow pattern as OAV-behavior (one asymmetric vortex). This behavior was also observed in numerous experimental tests [6,7,[16][17][18]25]. We recognize that an extensive study is required to elucidate the mechanism causing the loss of symmetry of the fluid flow pattern inside the nozzle.…”
Section: Analysis Of the Hydrodynamic Behavior Inside Fb And Wb-nozzlessupporting
confidence: 56%
See 2 more Smart Citations
“…We refer to this fluid flow pattern as OAV-behavior (one asymmetric vortex). This behavior was also observed in numerous experimental tests [6,7,[16][17][18]25]. We recognize that an extensive study is required to elucidate the mechanism causing the loss of symmetry of the fluid flow pattern inside the nozzle.…”
Section: Analysis Of the Hydrodynamic Behavior Inside Fb And Wb-nozzlessupporting
confidence: 56%
“…The numerical simulations presented in the previous section showed that the flow detector produces smooth and symmetric patterns on both exit ports. As was determined in the previous works [16,17], the properties of the jets emerging from the ports are mainly determined by the flow pattern formed at the bottom of the SEN. The results presented in the latter section explored only the interior flow features.…”
Section: Performance Analysis Using Sph Simulationsmentioning
confidence: 92%
See 1 more Smart Citation
“…As a consequence of the above behavior, the visualization of the process is performed in experimental facilities using water as the working fluid similarity criterion to obtain a scaled model of the system [3]. It is a frequent practice to reproduce the fluid dynamics within the mold using a scaled, physical model because of the reduced geometrical dimensions of the system and ambient temperature to prevent hazardous conditions during the process [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Gonzalez-Trejo et al [5] studied fluid dynamics within a pair of submerged entry nozzle models with a square crosssection bore. ey contemplated water as a working fluid with the Froude similarity criterion.…”
Section: Recent Advances In Multiphase Flows In Engineeringmentioning
confidence: 99%